Elevated circulating TLR4+ monocytes in patients with liver fluke Opisthorchis viverrini is associated with advanced periductal fibrosis - Salao, Kanin; Thapphan, Chakrit; Thai, Tran Duong; Faksri, Kiatichai; Suttiprapa, Sutas; Tangkawattana, Sirikachorn; Sripa B, Banchob; Edwards, Steven W (The Journal of Infection in Developing Countries, 2023)
Introduction: Opisthorchis viverrini (Ov) infection can lead to several disease manifestations of the bile duct including advanced periductal fibrosis (APF) and the most severe complication, cholangiocarcinoma (CCA). Monocytes migrate to the infection site and differentiate into tissue macrophages to express and release molecules such as cytokines, reactive oxygen species, and growth factors. TLR4+ monocytes are classified as having a pro-tumor phenotype and secrete tumor-promoting factors. The aim of this study is to investigate the role of monocytes in the pathogenesis of opisthorchiasis. Methodology: We used flow cytometry to measure the number of TLR4+ monocytes in the circulating blood of Ov infected patients with or without APF compared to healthy, non-Ov-infected controls. Results: We found, for the first time, that patients with AFP have elevated numbers of circulating TLR4+ monocytes when compared to patients without fibrosis and healthy individuals. Intriguingly, when we measured ROS from these monocytes, we found increased ROS production in patients with APF. Conclusions: We propose that excessive production of ROS from these TLR4+ monocytes may lead to excessive injury of surrounding tissue and hence contribute to the pathological processes that lead to the development of advanced periductal fibrosis.